2005
DOI: 10.1007/s10562-004-3445-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of titania in TiO2?SiO2 mixed oxides-supported metallocene catalyst during ethylene/1-octene copolymerization

Abstract: The present study showed enhanced activities of ethylene/1-octene copolymerization via TiO 2 -SiO 2 mixed oxides-supported MAO with a zirconocene catalyst. It was proposed that titania was decorated on silica surface and acted as a spacer to anchor MAO to the silica support resulting in less steric hindrance and less interaction on the support surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…For the EH copolymerization, the activity of the homogeneous catalytic system (without the support) was the highest among that obtained from the other supported catalytic systems. This is due to the supporting effect as mentioned by many authors [5,6]. Considering the various supports, the activities were in the order of TiO 2 -SiO 2 > SiO 2 > TiO 2 .…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…For the EH copolymerization, the activity of the homogeneous catalytic system (without the support) was the highest among that obtained from the other supported catalytic systems. This is due to the supporting effect as mentioned by many authors [5,6]. Considering the various supports, the activities were in the order of TiO 2 -SiO 2 > SiO 2 > TiO 2 .…”
Section: Resultsmentioning
confidence: 59%
“…It has been reported that many inorganic supports such as SiO 2 , Al 2 O 3 and MgCl 2 have been extensively studied. It was found that different supports could alter the catalytic behaviors during reaction as well [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The SEM micrographs of polymers are shown in Fig. 8 indicating the typical morphologies of copolymers obtained from this catalytic system [9,14]. There was no significant change in copolymer morphologies upon various supports employed.…”
Section: Resultsmentioning
confidence: 89%
“…It was found that silane modification resulted in increased activities for ethylene/1-hexene copolymerization. In addition, the copolymerization of ethylene/a-olefin via mixed TiO 2 /SiO 2 -supported zirconocene/MAO catalyst was also studied [13,14]. It was found that mixed TiO 2 / SiO 2 supports apparently resulted in increased polymerization activity as well.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of mixed oxide support was also mentioned [20][21][22] as one of the promising ways to obtain a suitable support due to its synergetic effect arising from the mixing property. In the recent year, a significant development in nanoscience and nanotechnology has been tremendous.…”
Section: Introductionmentioning
confidence: 99%